Addressing the need for biomarker liquid chromatography/mass spectrometry assays: A protocol for effective method development for the bioanalysis of endogenous compounds in cerebrospinal fluid. (9th July 2013) - Benitex, Yulia; McNaney, Colleen A.; Luchetti, David; Schaeffer, Eric; Olah, Timothy V.; Morgan, Daniel G.; Drexler, Dieter M.
Abstract : RATIONALE: Research on disorders of the central nervous system (CNS) has shown that an imbalance in the levels of specific endogenous neurotransmitters may underlie certain CNS diseases. These alterations in neurotransmitter levels may provide insight into pathophysiology, but can also serve as disease and pharmacodynamic biomarkers. To measure these potential biomarkers in vivo, the relevant sample matrix is cerebrospinal fluid (CSF), which is in equilibrium with the brain's interstitial fluid and circulates through the ventricular system of the brain and spinal cord. Accurate analysis of these potential biomarkers can be challenging due to low CSF sample volume, low analyte levels, and potential interferences from other endogenous compounds. METHODS: A protocol has been established for effective method development of bioanalytical assays for endogenous compounds in CSF. Database searches and standard‐addition experiments are employed to qualify sample preparation and specificity of the detection thus evaluating accuracy and precision. RESULTS: This protocol was applied to the study of the histaminergic neurotransmitter system and the analysis of histamine and its metabolite 1‐methylhistamine in rat CSF. CONCLUSIONS: The protocol resulted in a specific and sensitive novel method utilizing pre‐column derivatization ultra high performance liquid chromatography/tandem mass spectrometry (UHPLC/MS/MS), which is also capable of separating an endogenous interfering compound, identified as taurine, from the analytes of interest. Copyright © 2013 John Wiley & Sons, Ltd.